Duration of virus shedding after trivalent intranasal live attenuated influenza vaccination in adults - Talbot, Thomas R; Crocker, Deidre D; Peters, Jody; Doersam, Jennifer K; Ikizler, Mine R; Sannella, Edith; Wright, Peter E; Edwards, Kathryn M (Infection control and hospital epidemiology, 2005)
To characterize the probability and duration of viral shedding among adults given trivalent live attenuated influenza vaccine (LAIV). Prospective surveillance study. Nasal wash samples were collected from adult volunteers at baseline and on days 3, 7, and 10 and between days 17 and 21 following intranasal LAIV vaccination. The presence, titer, and identification of each specific strain of influenza virus shed were determined by standard methodology. Twenty subjects received LAIV. No samples were positive for influenza virus at baseline. After LAIV vaccination, influenza virus was recovered from 10 of 20 vaccinees on day 3, from 1 of 18 vaccinees on day 7, and from none of the samples on days 10 or 17 through 21. Vaccinees who shed vaccine virus were significantly younger than those who did not (mean age, 26.4 vs 38.6 years; P < .01). Although the presence of specific mucosal immunoglobulin A to influenza B was associated with significantly less shedding of influenza B after vaccination (P = .02), associations of shedding with other measures of immunity were not detected. The duration of shedding of vaccine virus after LAIV in adults i s limited and may be associatedwith an individual's prior influenza vaccination history.